#RevocaciónDeMandato in México 2022 Analysis: A look from Technopolitics - Rivera Magos, Sergio; González Pureco, Gabriela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In a social and technological context, that fosters hybrid political participation schemes and within the framework of the Mandate Revocation process in Mexico 2022, the behavior of the #RevocaciónDeMandato is studied, with the aim of analyzing the use of digital social networks as spaces for expression, debate and citizen participation from the theoretical perspective of Technopolitics. Using data mining tools, the general behavior of the hashtag, the presence of emotions, the sociodemographic profile of the participants in the social conversation, as well as the participation of the media, influencers, public figures, politicians and institutions are recovered.